Effect of strategic attitudes on marketing capabilities in Small And Medium Enterprises (SMES) / Hamed Dehghanan and Narges Jadidi - Dehghanan, Hamed; Jadidi, Narges (Institute of Research Management Innovation (IRMI), 2015)
Modern organizations need to use strategies and strategic thoughts to be successful in different and continuous challenges. Regarding the development and importance of strategic issues and their relationships with marketing activities of an organization, the present paper investigated the effect of strategic attitudes on marketing capabilities in active SMEs in detergent and cleaning products. Todoso, a standard questionnaire was designed and the data which have been gathered from 130 managers in active companies of this industry had been studied accordingly. The data were analyzed by structural equation method and Liserl software. The results showed the meaningful and positive effect of customer-orientation on expert marketing capabilities and related activities to the organizational architecture; meaningful and positive effect of competitor-orientation on expert marketing capabilities and related activities to the organizational architecture; and positive and meaningful effect of innovation-orientation on expert marketing capabilities with 95% certainty. But the effect of innovation-orientation on related activities to the organizational architecture was not meaningful at 95% certainty level.